Legal Protection for Victims of Sexual Violence in the Perspective of Indonesian Criminal Law - Pratama, Koko Wahyu; Darmawan, Didit; Saputra, Rio (Metromedia, 2022)
Sexual violence is a form of serious crime that involves serious impacts on victims, both physically and psychologically. In Indonesian criminal law, legal protection for victims of sexual violence has been regulated through various regulations, including the Child Protection Law and the Draft Law on the Elimination of Sexual Violence. However, the implementation of the law in the field still faces many challenges, such as the lack of sensitivity of law enforcement officials, weak protection of witnesses and victims, and lack of access to justice. This study aims to analyze the effectiveness of the existing legal framework in providing protection to victims of sexual violence. Through a normative juridical approach based on a literature study, this research reviews applicable regulations, implementation constraints, and best practices from various countries. The results show that despite progress in legislation, the implementation of legal protection for victims of sexual violence in Indonesia still requires significant improvement. This study suggests the importance of strengthening the training of law enforcement officers, improving access to rehabilitation services, and adopting restorative approaches to ensure justice for victims. Thus, the legal system can be more responsive in dealing with this crime.